The Role of Reputation in Shaping Peer-to-Peer Online Markets: A Meta-Analysis Perspective. - Julien, Baker (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2023)
Most online market exchanges are governed by reputation systems, which allow traders to comment on one another's behavior and attributes with ratings and text messages. These ratings then constitute sellers' reputations that serve as signals of their trustworthiness and competence. The large body of research investigating the effect of reputation on selling performance has produced mixed results, and there is a lack of consensus on whether the reputation effect exists and what it means. Reputation as a mechanism to govern market exchanges is undergoing its most successful propagation. Although humans' ability to share information about others' deeds and misdeeds has promoted market exchange throughout history modern information and communication technology (ICT) has reduced the costs of sharing information to a minimum.